A Critical Review of the Historical Formation of Olympic-Style Taekwondo's Institutions and the Resulting Present-Day Inconsistencies. Issue 12 (13th August 2017) - Moenig, Udo; Kim, Minho
Abstract: Taekwondo, an official Olympic sport and the nominal 'national sport' of the Republic of Korea, is not as uniform and single an entity as one might expect. In terms of corporate organization, a range of different competing associations have been founded over the years, but the governing body recognized by the International Olympic Committee is the World Taekwondo Federation (WTF). This article focuses on so popularly called 'Olympic taekwondo'. The WTF emerged out of the previously, nationally established and South Korean Government-supported Korea Taekwondo Association (KTA), which historically existed under different names and alignments. In conjunction with the WTF, a taekwondo 'technical' headquarters was also established, and named, 'World Taekwondo Headquarters' or 'Kukkiwon'. The formation of taekwondo's institutions happened during the turbulent decades after Korea's liberation from Japanese colonial rule in 1945, which, eventually, gave rise to a military regime, in 1961. The general atmosphere of those times was one of ultra-nationalism and militarism in which taekwondo became an instrument for the authoritarian regime. In this context, the paper critically analyzes the formation of taekwondo's institutions. Moreover, the discussion focuses on the outdated responsibilities and relationships between these institutions in modern times.